Humanitarian fables: morals, meanings and consequences for humanitarian practice - James, M (Taylor and Francis, 2022)
This article describes how events are turned into fables in humanitarian organisations. It explores how these fables circulate, the lessons they come to embody and their influence in maintaining an organisational status quo. The article argues that such stories teach new humanitarian employees certain ‘facts’ about ‘the field’ and help form and consolidate consensus about why things are the way they are in an organisation. By describing three such fables circulating amongst Médecins Sans Frontières ‘international’ employees in the Democratic Republic of the Congo, each of which suggested a need for foreign humanitarians to maintain a certain distance from local citizens (including their nationally hired colleagues) as a means of personal and organisational security, the article illustrates how such fables can ‘justify’ certain organisational decisions that ultimately reinforce structures of unequal power relations between different humanitarian employees.